Conventional vs 3-Dimensional Printed Cast Wear Comfort. (May 2020) - Graham, Jack; Wang, Mark; Frizzell, Kaela; Watkins, Cynthia; Beredjiklian, Pedro; Rivlin, Michael
Background: The objective of this study was to determine the functionality of 3-dimensional (3D) printed orthoses for upper extremity immobilization compared with conventional immobilization.Methods: Twelve healthy volunteers were fitted with a 3D custom printed short arm cast and a short arm fiberglass cast in separate sessions. The Jebsen Hand Function Test (JHFT) was used to test function and dexterity in each cast. All volunteers completed a modified version of the Patient-Rated Wrist Evaluation (PRWE). Skin complications were recorded.Results: There were no significant differences during the JHFT between casts, although one-third of the participants in the 3D cast could perform the tasks in a normal time, which they could not in the fiberglass cast. The average PRWE function score was lower in the 3D cast group than in the fiberglass group (45.5 vs. 80.8). Minor skin irritation was noted in 42% of patients in the fiberglass cast group compared with only 1 patient (8%) in the 3D cast group. One patient in the fiberglass group required a cast change due to inappropriate fit.Conclusions: Both casting techniques demonstrate similar objective function based on the JHFT. Patient satisfaction, comfort, and perceived function are superior in the 3D printed casts.